Globalization and Global health - Luna, Florencia (2015)
Globalization shrinks the world. The world watches on television people dying of hunger or in extreme poverty conditions. Every year, 8 million children die before they reach the age of 5 from preventable diseases. "Exotic illnesses" cease to be so exotic, they can cross borders easily. Ebola, originally an African worry, in 2014 was an international threat. The revolution in information technologies enables us witness the emergence of transnational epistemic communities exhibiting, measuring and explaining health and disease. Presently, the authors are more aware than ever of the health problems of people from far away countries, which decades ago were unknown and distant. The transparency and availability of this information exhibits, in a quasiobscene way, an unacceptable world. A world that is willing to rescue banks and ignores the worst off - those people whose unlucky birth seals a never ending cycle of misery with almost no possibility of breaking it. This paper address the situation just described by asking: Are these new empiric circumstances refected in the authors' moral understanding of the issues? How should the world think of global health and their obligations towards people living in deprivation? How can the new empiric possibilities the global world offers be related to the implementation of such obligations? What are some of the challenges to the translation of new obligations to the present world? In addressing these questions, the paper argues that if the world seriously wants to address the obligations towards those in need, even if they are far away from the places they may need to work not only with ideal proposals such as the "new obligations" pointed by Singer and Pogge, but also with different transitional theories and non-ideal strategies in order to solve some of the big challenges the real world impose to theories.